Genetic diversity of Leishmania tropica: Unexpectedly complex distribution pattern - Charyyeva, Arzuv; Çetinkaya, Ülfet; Özkan, Bora; Şahin, Serkan; Yaprak, Nermin; Şahin, Izzet; Yurchenko, Vyacheslav; Kostygov, Alexei Yu (Acta tropica, 2021)
In this study, we characterized a collection of clinical samples obtained from Syrian and Turkish patients with cutaneous leishmaniasis using internal transcribed spacer 1 (ITS1) sequences. All obtained sequences belonged to Leishmania tropica. Combining them with those available from GenBank allowed us performing a broad-scale analysis of genetic diversity for this species. We demonstrated that L. tropica has a complex phylogeographic pattern with some haplotypes being widespread across endemic countries and others restricted to particular regions. We hypothesize that at least some of them may be associated with alternative vectors or animal reservoirs.
Keywords: Animals; leishmanióza kožní; Phylogeography; Disease Vectors; lidé; Leishmania tropica; Genetic Variation; Leishmaniasis, Cutaneous; Male; ITS1; Haplotypes; Haplotype diversity; fylogeografie; infekce přenášené vektorem; haplotypy; zvířata; mužské pohlaví; Cutaneous leishmaniasis; genetická variace; Humans